2022
DOI: 10.1101/2022.05.09.491230
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CPSF3 inhibition blocks pancreatic cancer cell proliferation through disruption of core histone processing

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a lethal disease with limited effective treatment options. This potentiates the importance of uncovering novel drug targets. We have discovered global dysregulation of the gene regulatory process alternative polyadenylation (APA) in PDAC. APA is a pre-mRNA processing mechanism that generates mRNAs with distinct 3’ ends, impacting gene expression and protein function. We revealed that APA dysregulation in PDAC drives oncogenic signatures and predicts poor patient outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…CPSF-73 is also responsible for 3′ end processing of replicationdependent histone pre-mRNAs, whose mature forms do not have the poly(A) tail 57 . In fact, a recent study of pancreatic cancers showed drastic downregulation of these histone proteins after JTE-607 treatment 41 . Therefore, JTE-607-mediated inhibition of histone transcripts could further exacerbate S phase crisis, adding another layer of its function in suppressing proliferative cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPSF-73 is also responsible for 3′ end processing of replicationdependent histone pre-mRNAs, whose mature forms do not have the poly(A) tail 57 . In fact, a recent study of pancreatic cancers showed drastic downregulation of these histone proteins after JTE-607 treatment 41 . Therefore, JTE-607-mediated inhibition of histone transcripts could further exacerbate S phase crisis, adding another layer of its function in suppressing proliferative cells.…”
Section: Discussionmentioning
confidence: 99%
“…While CPSF-73 inhibitors have been used in multiple parasitic protozoans 37,38 , JTE-607 is the first known CPAi compound in human cells. JTE-607 has also been shown to suppress certain cancer cells, including those from acute myeloid leukemia 39 , Ewing's sarcoma 36 , some lung and hepatocellular carcinoma 36 , breast cancer 40 and pancreatic cancer 41 . However, some cancer cells appear quite tolerant of the compound 36 , raising the question as to what cellular features are deterministic for cell survival upon JTE-607 treatment.…”
mentioning
confidence: 99%
“…Another compound that targets CPSF73, JTE-607, prevents inflammation and also inhibits growth of Ewing's sarcoma, acute myeloid leukemia, and pancreatic ductal adenocarcinoma cell lines (109,113). JTE-607 induces global read-through transcription and R-loop formation in cancer cells (109).…”
Section: Cpsf73 As a Therapeutic Targetmentioning
confidence: 99%
“…JTE-607 induces global read-through transcription and R-loop formation in cancer cells (109). Many types of cancers overexpress CPSF73 (113,114). The elevated transcriptional activity of cancer cells may make their survival more dependent on pre-mRNA processing than that of nontransformed tissues, providing a therapeutic window where cancer cells are more susceptible to inhibition of CPSF73.…”
Section: Cpsf73 As a Therapeutic Targetmentioning
confidence: 99%